Meaningful use and meaningful curricula: a survey of health informatics programmes in the USA. (27th August 2012) - Koong, Kai S.; Ngafeeson, Madison N.; Liu, Lai C.
The introduction of the US government's Meaningful Use criteria carries with it many implications including the training curriculum of healthcare personnel. This study examines 108 health informatics degree programmes across the USA. First, the courses offered are identified and classified into generic classes. Next, these generic groupings are mapped to two important frameworks: the Learning to Manage Health Information (LMHI) academic framework; and the Meaningful Use criteria policy framework. Results suggest that while current curricula seemed acceptable in addressing Meaningful Use Stage 1 objective, there was insufficient evidence that these curricula could support Meaningful Use Stage 2 and Stage 3. These findings are useful to both curriculum developers and the healthcare industry. Curriculum developers in health informatics must match curriculum to the emerging healthcare policy goals and the healthcare industry must now recruit highly trained and qualified personnel to help achieve these new goals of data–capture, data–sharing and intelligence.